Books As Weapons: Reading Materials and Unfairly Prejudicial Character Evidence - Paul Varnado (Washington University Journal of Law & Policy, 2009)
This Note argues that reading histories should be barred as a matter of law from the criminal trial context because admission of such evidence unfairly prejudices a defendant in the eyes of a rational fact-finder.
Keywords: Reading interests; Reading histories; Surveillance of intellectual activity; Character evidence (Law); Right of privacy; Admissible evidence; Cognitive evidence; Federal Rules of Evidence